Insect community structure covaries with host plant chemistry but is not affected by prior herbivory - Visakorpi, K; Riutta, T; Martinez-Bauer, A; Salminen, J; Gripenberg, S (Ecological Society of America, 2019)
By feeding on plant tissue, insect herbivores can change several characteristics of their hosts. These changes have the potential to alter the quality of the plant for other herbivore species, potentially altering the structure of the community of species attacking the plant at a later point in time. We tested whether herbivory early in the season changes host plant performance, polyphenol chemistry, and the community structure of sessile herbivores later in the season. We experimentally manipulated densities of early‐season moth caterpillars on a set of young oak trees and measured tree growth, reproduction, leaf chemistry, and the abundance and community composition of leafmining and galling species later in the season. The experimental manipulations of early‐season herbivores did not affect late‐season leaf chemistry or tree performance. Early‐season herbivores had a weak negative effect on the abundance of gallers and a positive, tree‐dependent effect on the overall diversity of late‐season sessile herbivores. The chemical composition of leaves covaried with the species composition of the late‐season leafmining and galling community. Both the chemical composition of the host tree and the late‐season insect community structure were strongly affected by the growth location of the tree. Our results suggest that plant‐mediated indirect effects between herbivores might play a limited role in this system, whereas the underlying variation in plant chemistry is an important factor structuring the associated insect community. Our results emphasize that factors other than prior herbivory can be important determinants of plant chemistry and the community composition of herbivores.